2000
DOI: 10.1097/00000539-200009000-00028
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-Injection Axillary Brachial Plexus Block: A Comparison of Two Methods of Nerve Localization–Nerve Stimulation Versus Paresthesia

Abstract: Two methods of nerve localization were compared when performing an axillary brachial plexus block by the multiple-injection technique. Nerve stimulation provided a faster onset and a greater incidence of complete block, related to a better success rate for anesthetizing the radial and the musculocutaneous nerves, than paresthesia elicitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 14 publications
2
21
0
Order By: Relevance
“…Other authors have reported a higher success rate with a low current (0.3 mA -O.5 mA) [11,12]. Moreover, it is generally stated that, as the distance increases between the target nerve and the stimulating needle, a higher stimulus current is required [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have reported a higher success rate with a low current (0.3 mA -O.5 mA) [11,12]. Moreover, it is generally stated that, as the distance increases between the target nerve and the stimulating needle, a higher stimulus current is required [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral nerve stimulation techniques may be more comfortable for the patient because paresthesias are not intentionally sought. Block onset is also quicker and more complete [52]. Deliberate needle-elicited paresthesias are at least a questionable standard [53].…”
Section: Recommendation Cmentioning
confidence: 99%
“…The paresthesia method is less well accepted by patients because of discomfort during block performance [10]. The theoretical risk of nerve injury is also greater [52].…”
Section: Recommendation Cmentioning
confidence: 99%
“…Given that multiple needle passes seeking a nerve stimulation response or a paresthesia have been implicated in increasing the risks for neuropraxia, patient anxiety, and patient dissatisfaction [2][3][4], the observation that a needle may be physically touching a nerve without evoking a response is disconcerting. Therefore, the major objectives of this database review were to define the frequency of failed nerve stimulation during ultrasound guidance and to determine whether a successful motor response to nerve stimulation predicts a successful block.…”
Section: Introductionmentioning
confidence: 99%